Evaluasi Program Pendidikan Pemakai Dengan Model CIPP di Perpustakaan Fakultas Teknik UGM - Nova Indah Wijayanti; Rita Yulianti; Bagus Wijaya (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2019)
The optimal use of libraries is through user education, because through this program users get a series of knowledge about information sources. One way to find out the success of a program is to do an assessment. This study aims to evaluate the implementation of user education that has been implemented in the Library of the Faculty of Engineering UGM. CIPP Model (Context, Input, Process & Product) used for evalution with a qualitative approach. Research subjects were members of the UGM Faculty of Engineering who had attended user education programs and library management team. Data collection is done with documentation, interviews, and observations. The results showed (1) the Context evaluation was good, there was a match between the program with the vision and mission of the institution, (2) Evaluation of inputs was good, supporting facilities and facilities were adequate, (3) Process evaluation was sufficient, the implementation schedule needed to be improved, ( 4) Evaluation of the product is good, there is a certificate as a sign of following the activity by achieving the competency that has been set. The factors that support the implementation of the program are competency of human resources, communication, adequate facilities and infrastructure, and good cooperation with stakeholders. The factors that hinder the program are the schedule of activities that are not yet routine, those responsible for the program cannot be delegated to other people, there is no analysis of student needs, and there is no written policy on this program. The recommendation of this research is that it is necessary to improve several inhibiting factors so that the implementation of user education activities can run smoothly in accordance with the stated goals.